Planning, implementation, and first results of the Tropical Composition, Cloud and Climate Coupling Experiment (TC4) - Toon, Owen B. (2010)
El Centro de Investigaciones Geofísicas (CIGEFI) colaboró en el equipo de previsión meteorológica.